Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1063/1.1885000
|View full text |Cite
|
Sign up to set email alerts
|

Shear softening and structure in a simulated three-dimensional binary glass

Abstract: Three-dimensional model binary glasses produced by quenching from a range of liquid temperatures were tested in shear over a range of strain rates using molecular-dynamics techniques. Tests were performed under constant volume and constant pressure constraints. The simulations revealed a systematic change in short-range order as a function of the thermal and strain history of the glass. While subtle signs of differences in short-range order were evident in the pair distribution function, three-body correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 40 publications
6
39
0
Order By: Relevance
“…The peaks sharpen under quenching from the melt, but the distribution does not evolve significantly during aging. In contrast, simulations of metallic glass formers showed a stronger sensitivity of this parameter to the quench protocol [31], but most of those changes may be due to rearrangements in the supercooled liquid state and not in the glassy state.…”
Section: Structural Evolutionmentioning
confidence: 82%
See 1 more Smart Citation
“…The peaks sharpen under quenching from the melt, but the distribution does not evolve significantly during aging. In contrast, simulations of metallic glass formers showed a stronger sensitivity of this parameter to the quench protocol [31], but most of those changes may be due to rearrangements in the supercooled liquid state and not in the glassy state.…”
Section: Structural Evolutionmentioning
confidence: 82%
“…Recent simulation studies of metallic glasses have shown the existence of several short range order parameters that can distinguish between glassy states created through different quenching protocols [30,31,32]. A strong correlation has been found between "ordered" regions of the glass and strain localization.…”
Section: Structural Evolutionmentioning
confidence: 99%
“…In contrast, the homogenous shear flow in metallic glass typically occurs within the supercooled liquid region at high temperatures near the T g point and provides well plastic deformation properties. However, atomic simulations indicated that the shear localization of MGs not only depends on its thermal history but also on the lengthscale of sample [10,15,16].…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have investigated the relationship between the free volume and the formation of shear bands [7][8][9]. Atomic simulations also show that the local free volumes increase in the BMGs provides an open space for the movements of atoms and is associated with the localization of shear band, and the shear softening results from the production of excessive free volume in the shear band [10][11][12]. In the fatigue damage of BMGs, the shear band formation and propagation usually go along with the local increase of free volumes and crack sites within BMGs due to the weakness in the shear bands or shear-off steps [13,14], subsequently leading a fracture and fatigue damage.…”
Section: Introductionmentioning
confidence: 97%
“…Even in a small simulated system, local values of shear modulus G can extend to very low values, reflecting configurations that are near to instability [58]. Evidence for shear events at low strain comes from simulations [59], from viscoelastic measurements [60], and from the interpretation of the macroscopic values of elastic moduli of glasses [61]. The rearrangements contribute to elastic strains that are greater than would be seen otherwise (with affine displacements) and therefore give lower elastic moduli than in the crystalline counterpart materials.…”
Section: Mechanism Of Disorderingmentioning
confidence: 99%